Analysis of the Influence of Non-Cash Payment Systems, Inflation and Interest Rates on the Money Supply (M1) 2013-2022 - Bujung, Reinhard Eliezer Yusup; Rotinsulu, Tri Oldy; Th. B. Maramis, Mauna (Formosa Journal of Applied Sciences, 2024)
The money supply (M1) is the main metric for assessing a country's economic well-being. The money supply measured in the M1 category is the total amount of currency and short-term deposits that are easily accessible to the public for daily transactions. In 2013–2022, this research aims to calculate the M1 impact of non-cash payment methods, inflation and interest rates. A multiple regression analysis model is used for this analysis. The findings of this research show that there is a positive correlation between the money supply (M1) in Indonesia and non-cash transactions. The money supply (M1) in Indonesia is positively impacted by inflation, although the correlation is not too strong. Interest rates have a significant effect on Indonesia's money supply (M1) and are negatively correlated with M1. Non-cash payments, inflation and interest rates also have a significant relationship with M1. .